A Rapid Replacement of Vimentin-Containing Radial Glia by Glial Fibrillary Acidic Protein-Containing Astrocytes in Transplanted Telencephalon. (1997) - Tuba, Andrea; Kállai, Lázló; Kálmán, Mihály
Abstract : The present study follows the early events in the development of astroglia in rat embryonic (El5) tissue grafted into the cortex of adult rats. Astroglial elements (radial glia and astrocytes) were studied by glial fibrillary acidic protein (GFAP) and vimentin immunohistochemistry on post-transplantation (PT) days 7, 11, 14, 17, and 21. At PT7, GFAP-immunopositive elements were only scarce fibers in the transplants. At PTll, a dense network of long, GFAP-immunopositive fibers enmeshed the entire transplant, and astrocytes were already recognized. The fibers also showed vimentin immunoreactivity. By PT14, astrocytes became the predominant GFAP-labeled elements, although a few long fibers persisted. When compared with in situ development, the grafts showed earlier GFAP-immunoreactivity and earlier appearance of astrocytes, as well as a more rapid transition from the immature to the mature form of the glial system.